Weight management in obesity – past and present - Haslam, D. (Int J Clin Pract, 2016)
AIMS: To describe the treatment of obesity from ancient times to present day. METHODS: Articles reporting the development of anti‐obesity therapies were identified through a search for ‘anti‐obesity’ AND ‘pharmacotherapy’ AND ‘development’ within the title or abstract on PubMed and ‘obesity’ in ClinicalTrials.gov. Relevant articles and related literature were selected for inclusion. RESULTS: Stone‐age miniature obese female statuettes indicate the existence and cultural significance of obesity as long as 30,000 years ago. Records from Ancient Egyptian and Biblical eras through Greco‐Roman to Medieval times indicate that obesity was present throughout the major periods of history, although peoples of previous centuries would probably have experienced overweight and obesity as exceptional rather than normal. Health risks of obesity were noted by the Greek physician Hippocrates (460–377 BCE) when the earliest anti‐obesity recommendations on diet, exercise, lifestyle and use of emetics and cathartics were born. These recommendations remained largely unchanged until the early 20th century, when spreading urbanisation, increasingly sedentary jobs and greater availability of processed foods produced a sharp rise in obesity. This led to the need for new, more effective, ways to lose weight, to address comorbidities associated with obesity, and to attain the current cultural ideal of slimness. Drug companies of the 1940s and 1950s produced a series of anti‐obesity pharmacotherapies in short succession, based largely on amphetamines. Increased regulation of drug development in the 1960s and new efficacy requirements for weight‐loss drugs led to rapid reduction in anti‐obesity therapies available by the early 1990s. CONCLUSION: In the last two decades, several new and emerging therapies have been approved or are in development to provide safe, long‐term pharmacological agents for the treatment of obesity.